Strengthening humanitarian networks: Applying the network functions approach - and Ramalingam, Ben; Mendizabal, Enrique; Schenkenberg van Mierop, Ed (ODI, 2008)
This note offers a simple, flexible and powerful methodology — the network functions approach (NFA) — that can be applied to analyse and strengthen humanitarian and development networks. Based on research undertaken at ODI and elsewhere, the NFA suggests there are six overlapping functions that different networks perform in varying combinations. Through reflection on a network’s current activities and how they relate to each of these functions, the NFA helps those facilitating, acting within or supporting networks to work towards an ‘ideal’ functional mix. The aim is for network strategies to be honed, thinking clarified, activities sharpened and ultimately, humanitarian performance improved.